Cyber anti-intellectualism and science communication during the COVID-19 pandemic: a cross-sectional study - Yan Kuang (Frontiers in Public Health)
BackgroundDuring the COVID-19 pandemic, science communication played a crucial role in disseminating accurate information and promoting scientific literacy among the public. However, the rise of anti-intellectualism on social media platforms has posed significant challenges to science, scientists, and science communication, hindering effective public engagement with scientific affairs. This study aims to explore the mechanisms through which anti-intellectualism impacts science communication on social media platforms from the perspective of communication effect theory.MethodThis study employed a cross-sectional research design to conduct an online questionnaire survey of Chinese social media users from August to September 2021. The survey results were analyzed via descriptive statistics, t-tests, one-way ANOVA, and a chain mediation model with SPSS 26.0.ResultsThere were significant differences in anti-intellectualism tendency among groups of different demographic characteristics. The majority of respondents placed greater emphasis on knowledge that has practical benefits in life. Respondents’ trust in different groups of intellectuals showed significant inconsistencies, with economists and experts receiving the lowest levels of trust. Anti-intellectualism significantly and positively predicted the level of misconception of scientific and technological information, while significantly and negatively predicting individuals’ attitudes toward science communication. It further influenced respondents’ behavior in disseminating scientific and technological information through the chain mediation of scientific misconception and attitudes toward science communication.ConclusionThis research enriches the conceptual framework of anti-intellectualism across various cultural contexts, as well as the theoretical framework concerning the interaction between anti-intellectualism and science communication. The findings provide suggestions for developing strategies to enhance the effectiveness of science communication and risk communication during public emergencies.